Al2O3:Cr3+/tellurite glass composites: An efficient light converter for silicon solar cell. Issue 9 (November 2015) - Han, Boning; Yang, Yanmin; Wu, Jianhong; Wei, Jun; Li, Zhiqiang; Mai, Yaohua
Abstract: Al2 O3 :Cr 3+ nanocrystals have been developed as spectral converters for improving silicon cell photovoltaic conversion efficiency. In the Al2 O3 lattice, Cr 3+ ions act as broadband spectral acceptors by absorbing UV–vis (320–670 nm) photons, which are effectively converted into the strong red emission centered at around 696 nm, indicating Al2 O3 :Cr 3+ can be a good material for overcoming the so-called spectral mismatch in the silicon solar cell. The Al2 O3 :Cr 3+ nanocrystals are successfully introduced into tellurite glass to form transparent composites with good optical performance which can be characterized by photoluminescence (PL) spectra. These tellurite glass composites open a brand new field for the research of improving silicon solar cell photovoltaic conversion efficiency.